Remote Medical Diagnosis: A Case Study and Application Potential in Libya - Mohamed S. M. Hasni; Aeman .I .G .Masbah; Aymen Fathalla H. Alhasadi; Omar S Mosa Alsharif (Journal of Libyan Academy Bani Walid, 2025)
Artificial Intelligence (AI) has revolutionized many sectors, especially healthcare. This paper studies how AI techniques can improve remote medical diagnosis, focusing on their applicability in Libya. We propose a simple methodology for a diagnostic tool based on Convolutional Neural Networks (CNNs), supply mathematical formulations, and assess Libya’s healthcare infrastructure and socio-economic setting to evaluate feasibility. We also discuss main challenges—such as limited infrastructure, data privacy concerns, and cultural acceptance—and give recommendations to ensure strategic implementation for maximum benefit. This work aims to offer a roadmap for policymakers, healthcare providers, and technologists in Libya and similar developing countries..